(untitled) (Mantichora. Italian Journal of Performance Studies, 2024)
Claudia Ruggeri’s poetry represents, for several reasons, a case study suitable to be analyzed through the method of Performance Studies. This contribution focuses on the oral origin of her poetry which is born in view of a performative execution and in which the voice plays a leading role. Her poems have a dramatic setting and demand a real work on the part of the reader/listener.